Platelet Phospholipids and Stypven Clotting Time - Hovmand, L. L; Brøns, K; Gormsen, J (Thrombosis and Haemostasis, 1969)
1. Phospholipids in the thrombocytes were studied in 16 healthy individuals, 18 patients with hepatic cirrhosis and 11 patients suffering from a variety of illnesses which are generally considered to be connected with thrombocytopathy.2. In patients with hepatic cirrhosis the total amount of phospholipids was significantly lower: 8 (µg ± 2 µg lipid P per 109 platelets compared to 12 (µg ± 2 (µg lipid P per 109 platelets in healthy individuals.3. The percentage composition of the phospholipids was the same for healthy individuals as for the diseased persons.4. Decrease in platelet factor 3 activity as estimated by a modified stypven clotting time has been demonstrated using the thrombocytes from the patients suffering from hepatic cirrhosis whereas the activity was normal in uremic patients tested. The decreased clotting activity might partly be due to the reduced total amount of phospholipids. Surface active agents exert a much more profound reduction in clotting activity of phospholipids. It is concluded, that surface charge of phosphatide micelles determines their clotting activity more than concentration of all or a single phospholipid.